Lipid Profile in Postmenopausal Diabetic Female. - Simkhada, Rabindra; KC, Sanjay Singh; Yadav, Dharma Nath; Sahi, Ravi (Nepalese Heart Journal, 2021)
Background and Aims: Postmenopausal diabetic female are at increased risk of cardiovascular disease. The objective of this study was to study their lipid profile and prevalence of dyslipidemia and assess relation of control of lipid components with various risk factors. Methods: A cross sectional prospective study conducted at Shahid Gangalal National Heart Centre from 15th July 2020 to 14th October 2020 including 109 postmenopausal diabetic female. Detailed history along with clinical examination were conducted. Fasting lipid profile and other relevant investigations were obtained. Results: Mean age of participants was 63.48±9.26 years. Mean age of menopause was 48.59±1.88 years. A total of 37 (33.9%) were hypertensive, 17 (15.6%) were smoker, 67 (61.5%) were physically inactive. A total of 91 (83.5%) were non-vegetarian. Thirty eight (34.9%) had their blood sugar controlled with hemoglobin A1c of <7%. The mean total cholesterol and high density lipoprotein were 5.21±0.97 mmol/l and 1.02±0.13 mmol/l. Similarly mean triglyceride and low density lipoprotein were 2.24±0.75 mmol/l and 3.04±0.12 mmol/l. Dyslipidemia was present in 82.6%. Significant correlation of control of blood sugar with total cholesterol control status (R=0.28, P=0.01), low density lipoprotein control status (R=0.38, P=0.01), high density lipoprotein control status (R=0.36, P=0.04) and triglyceride control status (R=0.30, P=0.04) were seen. Conclusion: Dyslipidemia was common in post menopausal diabetic female. Blood sugar control status showed significant correlation with lipid profile parameters. A good sugar control and evaluation for lipid abnormalities is recommended in postmenopausal diabetic female.